ANALISIS TANGGUNG JAWAB PLATFORM TIKTOK TERHADAP PENYIARAN ULANG SECARA LANGSUNG (RESTREAMING) KONTEN LIVESTREAM WINDAH BASUDARA - NIM. A1011211254, UMAR (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT The advancement of information technology has led to the emergence of digital platforms such as TikTok, which allow users to instantly create, distribute, and monetize content, including through livestreaming features. However, this development also poses significant challenges to copyright enforcement, particularly with the practice of unauthorized real-time rebroadcasting (restreaming) of other creators